Pengaruh Metode Pembelajaran Demonstrasi terhadap Hasil Ujian Praktikum Mata Kuliah Keperawatan Dasar - Ernawati, Ernawati (JEDLISH : Journal Of Education and English Language Teaching, 2022)
Variations in learning methods require lecturers or educators to be observant and creative in their implementation. The demonstration method is a learning component that supports the transfer of knowledge that requires skills. The purpose of this study was to determine the effect of the demonstration learning model on the improvement of practical learning outcomes in Basic Nursing courses. This research is a type of quantitative descriptive research. The sample used in this study was total sampling, namely all second semester students, totaling 140 students. This study used a checklist instrument for assessing learning outcomes for each practicum skill. The collected data were analyzed using the t-test. The results of the analysis of post-test scores on infusion practical skills p=0.000<0.05, NGT p=0.001<0.05, Catheter p=0.010<0.05, Wound care p=0.001<0.05, Injection p=0.00< 0.05, oxygen p=0.001<0.05 and physical examination p=0.00<0.05. The conclusion from the study is that there is an influence of the demonstration learning model on improving learning outcomes for the Basic Nursing course practicum.